Optimization of machining parameters in CNC milling of Ti-6Al-4 V alloy using multiple methodology. (2022) - Kumar Yadav, Deepak; Kumar Dixit, Nitesh; Agarwal, Deepak; Kumar Khare, Sanchit
Abstract: Different optimization techniques are available for advancement the different machining parameters of milling process. The milling operations were performed and various characteristics namely MRR and SR were measured. Present work reveals, this paper deals a comparison of GRA, Taguchi Methodology and Topsis Methodology. The target of this exploratory work is to further developing the operating boundaries on a solitary activity and analyze the solution. Accordingly, the advancement is finished with various ultimate objectives that the resulting upgraded boundaries will advance a compromise between the efficiency and surface quality. The outcomes got created the most doable blends of the cutting boundaries and the work piece material that gave the most un-surface unpleasantness. Henceforth, the fruitful finishing of this work gives a mathematical methodology which is approved tentatively. In this examination paper a correlation is done between gra, Topsis and Taguchi Technique. The point of this work is to discover streamlining the machining boundary on a solitary activity and analyze the results. In this way the progression is finished with the ultimate objective that the ensuing upgraded boundaries will advance a compromise between the efficiency and surface quality. It is visualized that the solution in this investigation will help makers in anticipating and limiting the greatness of surface unpleasantness over machining activities.